2005
DOI: 10.1007/s00259-005-1882-0
|View full text |Cite
|
Sign up to set email alerts
|

11C-methionine PET for the diagnosis and management of recurrent pituitary adenomas

Abstract: We suggest that MET-PET is a sensitive technique complementary to MRI for the detection of residual or recurrent pituitary adenomas. It should gain a place in the efficient management of these tumours.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
59
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(63 citation statements)
references
References 40 publications
2
59
0
2
Order By: Relevance
“…Tsuyuguchi et al [157] and Tang et al [158] have performed comparisons in recurrent brain metastasis and pituitary adenomas and found that MET was useful in differentiating recurrent tumor from radiation injury. Overall, in spite of few and small-sized studies and absence of histopathological confirmation in many instances, there is evidence that METYPET has a high sensitivity for detecting tumor recurrences.…”
Section: Differentiation Of Tumor Recurrence Versus Radiation Injurymentioning
confidence: 98%
“…Tsuyuguchi et al [157] and Tang et al [158] have performed comparisons in recurrent brain metastasis and pituitary adenomas and found that MET was useful in differentiating recurrent tumor from radiation injury. Overall, in spite of few and small-sized studies and absence of histopathological confirmation in many instances, there is evidence that METYPET has a high sensitivity for detecting tumor recurrences.…”
Section: Differentiation Of Tumor Recurrence Versus Radiation Injurymentioning
confidence: 98%
“…Tang et al [11] concluded that 11 C- L -methionine is a sensitive technique for the detection of recurrent adenoma tissue and, complementary to MRI, should gain a place in the efficient management of these tumors [12]. Several other groups have underlined the value of PET in the diagnosis and management of intracranial tumors including pituitary adenomas [13,14,15,16,17].…”
Section: Discussionmentioning
confidence: 99%
“…The results of scintigraphy with 123 I-methoxybenzamide ( 123 I-IBZM) [11] showed a somewhat varying correlation between the number of D 2 receptors identified in different types of pituitary adenomas and the response to dopamine agonist treatment [22,23,24,25]. For the GH adenomas in some of these materials, no significant uptake of 123 I-IBZM was identified, although sensitivity to quinagolide was found in some of the same GH adenomas.…”
Section: Discussionmentioning
confidence: 99%
“…octreotide scintigraphy, 18 F-fluorodeoxyglucose positron emission tomography ( 18 F-FDG-PET)) has been employed by some workers, but with variable success, which in part reflects the limited spatial resolution of traditional scintigraphy and pituitary CT and the relatively high background uptake of 18 F-FDG by normal brain tissue. 11 C-methionine has been proposed as an alternative PET tracer for the localisation of pituitary adenomas (11,12). In contrast to 18 F-FDG, it is preferentially taken up by the normal pituitary gland, with relatively low uptake by the surrounding brain.…”
Section: Introductionmentioning
confidence: 99%